A study to evaluate the knowledge of ASHA workers on antenatal and postnatal care in Bijapur district - KJ, Shashank; Angadi, Mahabaleshwar Mahantappa (International Journal of Research in Medical Sciences, 2017)
Background: The discourse on the ASHA’s role centres around three typologies - ASHA as an activist, ASHA as a link worker or facilitator, and ASHA as a community level health care provider. She will counsel women on birth preparedness, importance of safe delivery, breastfeeding and complementary feeding, immunization, contraception and prevention of common infections including reproductive tract infection/sexually transmitted infection (RTIs/STIs) and care of the young child. Hence this study was conducted to evaluate the knowledge of antenatal and postnatal care of ASHA workers. Methods: A cross sectional study was done on 132 ASHA workers selected from 5 random PHCs in Bijapur taluk. Data was collected in a prestructured proforma using interview technique from June to October, 2012. Results: Most of the ASHA (68.1%) considered minimum of 3 postnatal visits after the normal vaginal delivery. Around 73.4% were aware that the new born child is to be wrapped up in the cloth soon after birth to prevent hypothermia. Majority (735.%) were aware about the duration of exclusive breastfeeding to be practiced by the lactating mother. 69.7% of the respondents said the duration of breastfeeding should be between 18-24 months. Conclusions: Self-explanatory, specific financial guidelines should be made available within time to the programme managers. Under the cascade model of training to the ASHA, trainings should provide complete knowledge and skills to the trainees within the stipulated time. Quality of training should be enhanced and refresher trainings should be planned regularly.